Cold ironing: Modelling the interdependence of terminals and vessels in their choice of suitable systems - Jeroen Pruyn; Jelle Willeijns (Journal of Shipping and Trade (JST), 2022)
Cold ironing has the potential to reduce the impact of ship exhausts in densely populated areas. However, especially for tankers, the implementation of this concept is almost non-existent. Still, these vessels have a relatively high port energy use, despite relatively short port visits, as they provide power to both pumps and inert gas systems during unloading and loading. A key factor in the reluctance, besides the fact that a sparkless connection is required, is the lack of a standard and the uncertainty from both tanker owners visiting a berth and terminal owners on which shore power systems to apply. This paper investigates the interdependency between ship and terminal owner choices for systems and establishes the overall most economical solution. Cold ironing was reviewed to identify existing systems and solutions and analyse the tanker fleet and terminals. The insights were combined in an integrated economic model consisting of two sub-models; one relating terminal decisions to a cold ironing price and one establishing the vessel side costs and savings. By using fuel price as an input and acceptance rates (for both terminals and vessels) for cold ironing systems as key variables to determine. The models have been used to identify the potential of cold ironing for shortsea and parcel tankers against different fuel prices and % of fleet and terminals that have shore power equipment. In all cases, shore power was not economical, which was caused by the high costs of the fixed costs of electricity, due to the high powers required. Interesting avenues for further research would be to increase the individuality of the model using e.g. an agent based model. Also extending the model with a battery pack on the terminal to allow for peak-shaving could lead to much lower costs and higher economic potential.
Keywords: 650; Cold ironing; Emission reduction; Port strategy; Ship owner